1989
DOI: 10.1063/1.343425
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reactions on annealing molybdenum-silicon multilayers

Abstract: The structure and interfacial reaction in sputtered Mo-Si multilayers have been studied using cross-section transmission electron microscopy, electron diffraction, Rutherford backscattering, and low-angle x-ray diffraction. Low-temperature (T<550 °C) annealing was performed in a rapid-thermal-annealing furnace and in situ in the microscope. No solid-state amorphization was observed, in spite of the presence of amorphous alloy interfacial layers in the as-deposited structure. Instead, the amorphous inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(65 citation statements)
references
References 29 publications
10
54
1
Order By: Relevance
“…The fractional change in bilayer spacing is graphically illustrated in Fig. 1 along with the data of Stearns et al [ 1] and Holloway et al [2]. The contraction trends of this study are qualitatively consistent with those of the earlier work.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The fractional change in bilayer spacing is graphically illustrated in Fig. 1 along with the data of Stearns et al [ 1] and Holloway et al [2]. The contraction trends of this study are qualitatively consistent with those of the earlier work.…”
supporting
confidence: 80%
“…Consequently, it is believed important to assess the structural stability of these mirrors. Relatively recent work by the authors and other investigators assessed the stability of Mo/Si multilayers [1][2][3][4][5]. Most of these works emphasized temperatures above 400°C and relatively short annealing times.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature at which the reflectivity of the first order Bragg peaks break down for these mirrors are lower than the baking temperature for our mirrors, which were e--beam deposited and thermally treated during deposition. In the literature activation energies E a for diffusion were deduced by means of an Arrheniusplot of the multilayer d-spacing ln(Ad) 2 versus 1/baking temperature [6,10,11]. The RBS spectra in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal stability of Mo/Si multilayers has been studied earlier in several works [5][6][7][8][9][10][11] but in all of them the multilayers are fabricated by sputtering. In [12] it is shown that thermal treatment during e--beam deposition can considerably enhance the reflectivity of Mo/Si multilayer * Present address: European Synchrotron Radiation Facility, F-38043 Grenoble, France mirrors with a double layer spacing of about 7.5 nm.…”
Section: Pacsmentioning
confidence: 99%
“…Thermal evaporation sources yielded abrupt interfaces, independent of the order of deposition. Two TEM studies 17,18 of Mo-Si interfaces on sputtered samples both conclude that the interfaces are 17 Å thick when Mo is deposited on Si, and 10 Å thick when Si is deposited on Mo. The lower conductivity in the sputtered samples may therefore result from scattering from substitutional impurities ͑silicon in molybdenum͒ as well as perhaps a greater degree of configurational disorder.…”
Section: G(dt)/g(d290) Versus T Inmentioning
confidence: 99%